2017
DOI: 10.15252/embr.201643270
|View full text |Cite|
|
Sign up to set email alerts
|

USP 26 regulates TGF ‐β signaling by deubiquitinating and stabilizing SMAD 7

Abstract: The amplitude of transforming growth factor‐β (TGF‐β) signal is tightly regulated to ensure appropriate physiological responses. As part of negative feedback loop SMAD7, a direct transcriptional target of downstream TGF‐β signaling acts as a scaffold to recruit the E3 ligase SMURF2 to target the TGF‐β receptor complex for ubiquitin‐mediated degradation. Here, we identify the deubiquitinating enzyme USP26 as a novel integral component of this negative feedback loop. We demonstrate that TGF‐β rapidly enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 43 publications
6
50
0
Order By: Relevance
“…In line with our previous results, we demonstrate that low USP26 expression is associated with poorer overall survival in glioblastoma, at the median threshold (high vs low), showing statistical significance with an overall P-value of 0.0259 (REMBRANDT) (new [3]). In line with our previous results, we demonstrate that low USP26 expression is associated with poorer overall survival in glioblastoma, at the median threshold (high vs low), showing statistical significance with an overall P-value of 0.0259 (REMBRANDT) (new [3]).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In line with our previous results, we demonstrate that low USP26 expression is associated with poorer overall survival in glioblastoma, at the median threshold (high vs low), showing statistical significance with an overall P-value of 0.0259 (REMBRANDT) (new [3]). In line with our previous results, we demonstrate that low USP26 expression is associated with poorer overall survival in glioblastoma, at the median threshold (high vs low), showing statistical significance with an overall P-value of 0.0259 (REMBRANDT) (new [3]).…”
supporting
confidence: 92%
“…While our new analysis of the REMBRANDT database does not show a correlation between lower patient survival and high TGFBRI, TGFBRII, or TGFBRIII expression at the median threshold (new Fig EV5B-D in Kit Lend Lui et al [3]), our additional analysis of the TCGA (cBioPortal) dataset would suggest a correlation for TGFBRII, as claimed in our paper (high versus low; Fig 2C). As noted, we did not realise that the REMBRANDT dataset was comprised of glioblastoma and lower-grade gliomas.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Extensive research into TGF-b signalling gives rise to many clinical trials, and among them over 20 are for cancer treatment [1]. In an attempt to show clinical significance, Kit Leng Lui et al [2] further suggest that the loss of USP26 correlates with high TGF-b activity and poorer patient survival/prognosis in glioblastoma. A paper by Kit Leng Lui et al [2] reports the involvement of the deubiquitinating enzyme USP26 as a key modulator of TGF-b activity through stabilisation of the negative feedback inhibitor Smad7.…”
mentioning
confidence: 99%
“…Studies in cancer cells have also shown that Smad7 levels are controlled by USP26, a deubiquitinating enzyme, which preventes Smad7 degradation [29]. On the other hand, there are intracellular mechanisms that counteract Smad7 activity.…”
Section: Smad7 Limits Tgf-β1 Activity In the Gutmentioning
confidence: 99%